Pyogenic sacroiliitis: Lessons learned from an atypical case series - Joana Arcângelo; Susana Norte Ramos; Pedro Alves; Delfin Tavares; Catarina Gouveia (Elsevier, 2019)
Introduction: Pyogenic sacroiliitis (PSI) is a rare condition that accounts for 1-2% of all joint infections in the paediatric age group. Its diagnosis is often difficult and delayed due to its nonspecific signs, symptoms and physical findings. Also, the identification of the causative microorganism is frequently challenging due to a high rate of negative blood cultures and the risks involved in joint aspiration in this location. Patients and methods: We performed a retrospective review of the health records of all patients aged less than 18 years admitted to a tertiary children's hospital due to PSI between 2008 and 2016. Results: Six cases of paediatric PSI were identified. The blood cultures were negative, and identification of the causative agent required joint fluid aspiration in one case of Aggregatibacter aphrophilus infection and specific screening tests for other less frequent agents: Kingella kingae (n = 2), Brucella melitensis (n = 1) and Bartonella henselae (n = 1). The patients were treated with specific antimicrobial regimens, and all had favourable clinical outcomes and were free from sequelae during the follow-up. Conclusions: Despite the small sample size, our study emphasizes the low effectiveness of blood cultures for diagnosis of paediatric PSI. It also highlights the need for a high level of suspicion for atypical agents and the early use of adequate diagnostic methods, including imaging and serological testing or polymerase chain-reaction (PCR) analysis of blood samples, as well as the prescription of an effective antimicrobial therapy. Resumen: Introducción: La sacroileítis piógena (SIP) es una entidad infrecuente que representa del 1 al 2% del total de las infecciones articulares en la edad pediátrica. Su diagnóstico a menudo se complica y retrasa debido a la inespecificidad de sus síntomas, signos y exploración física. Además, la identificación microbiológica puede resultar difícil debido a la alta proporción de hemocultivos negativos y los riesgos implicados en la aspiración de líquido articular en esta localización. Pacientes y métodos: Revisión retrospectiva de las historias clínicas de todos los pacientes menores de 18 años ingresados en un hospital infantil terciario con SIP en el período 2008-2016. Resultados: Se identificaron 6 casos de SIP en niños. Los hemocultivos fueron negativos, y la identificación del agente etiológico requirió aspiración de líquido sinovial en un paciente con infección por Aggregatibacter aphrophilus y pruebas específicas para la detección de agentes menos frecuentes en los pacientes restantes: Kingella kingae (n = 2), Brucella melitensis (n = 1) y Bartonella henselae (n = 1). Los pacientes recibieron regímenes de antibioterapia específica, y todos presentaron una evolución favorable y libre de secuelas durante el seguimiento. Conclusiones: A pesar del reducido tamaño muestral, nuestro estudio puso de relieve la baja efectividad del hemocultivo en el diagnóstico de la SIP pediátrica. También evidenció la necesidad de mantener un elevado índice de sospecha de los agentes atípicos y de emplear precozmente métodos diagnósticos apropiados, como las pruebas de imagen y la reacción en cadena de la polimerasa (PCR) en muestras de sangre, así como la prescripción de antibioterapia efectiva.